Analisis Metode Penyusutan Aset Tetap terhadap Laba di PT. Perkebunan Nusantara XIII Kebun Pelaihari - Bella Puspita Rininda; Fitriyani, Yuli; Zein, Mufrida; Zahera, Ria (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The determination of fixed asset depreciation methods will affect the profit earned by the company. The objective of this research is to investigate how the application of fixed asset depreciation methods influences the profit at PT. Perkebunan Nusantara XIII Kebun Pelaihari. This study employs a qualitative descriptive method using primary and secondary data from PT. Perkebunan Nusantara XIII Kebun Pelaihari from 2020 to 2022. The results indicate that the company uses PSAK Number 16 as the basis for calculating fixed asset depreciation, with the Straight-Line Method chosen as the method to determine depreciation expense. This method has proven to be effective in calculating fixed asset depreciation expenses and significantly impacts the company's profit. The calculations show that depreciation using the Straight-Line Method is lower, amounting to 33,042,024 IDR, compared to the Double Declining Balance Method of 66,084,048 IDR, and the Sum of the Years' Digits Method of 63,458,682 IDR.